Attention and Outcomes Across Learning Conditions in L2 Vocabulary Acquisition: Evidence from Eye-Tracking - Yiyang Yang; Hulin Ren (Journal of Eye Movement Research, 2025)
The role of attention has been shown to be essential in second language (L2) learning. However, the impact of different learning conditions on attention and learning outcomes remains underdeveloped, particularly through the application of eye-tracking technology. This study aims to evaluate the effect of intentional learning conditions (i.e., data-driven learning) on vocabulary learning and attentional allocations. Twenty-six intermediate English L2 learners participated in the study to learn the usage of four artificial attributive adjectives in noun phrases (NPs). Learning outcomes were analysed to assess the types of knowledge developed, shedding light on the role of attention and the conscious processing of word usage. Eye-tracking data, collected using Eyelink 1000 plus, investigated gaze patterns and the allocation of attentional sources when applying the learned usage of adjectives. The results indicate that fixation stability and regression movements significantly differ under the impact of intentional learning conditions. Post-test results also indicate a shift in attention from the target adjectives to the associated nouns. These findings underscore the critical role of attention and highlight the influence of learning conditions on L2 vocabulary learning, providing practical implications and empirical validation for L2 educators and researchers aiming to enhance vocabulary instruction through intentional learning strategies.